Semiotic Analysis of the Mangabing Partadingan Tradition in the Simalungun Region - Putri Caroline Tarigan (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyze the symbols in the Mangabing Partadingan tradition of the Simalingun tribe in the Simalungun area, North Sumatra. The analytical theory used is Charles Sanders Pierce's semiotic triangle, which consists of the following elements: Representation, Object, and Interpretant. This research uses descriptive qualitative methods. The analytical theory used is Charles Sanders Peirce's semiotic triangle, which includes representament, object and interpretant. This research uses a qualitative descriptive method. This research data was collected through observation, interviews and documentation. The research results show that there are 13 symbols in the Mangabing Partadingan tradition, namely: (1). Tenger rice sanggolom, (2). Pining Hinupas, (3). Pining Binatis Sanggolom, (4). Huning ovaries, (5). Gambir, (6). Cotton, (7). Timbahaou, (8). Cotton, (9). Selamatu, (10). Demban Gunringan, (11). Doraham, (12). Bonang Manalu, (13). Partadingan. Each symbol in the Mangabing Partadingan tradition of the Simalungun tribe has its own meaning.